Pengaruh Media Sosial Instagram Sebagai Sumber Informasi Terhadao Keputusan Pembelian Produk Wisata Fly Bali - Christopher, Ned; Wiarti, Luh Yusni Wiarti; Suasapha, Anom Hery (Journal of Applied Science in Tourism Destination, 2024)
In the current digital era, the internet is a daily necessity that has become ingrained in society. The internet is used to support activities from various sectors, such as economic and business activities. One of the digital tourism platforms that is being widely used as a promotional medium is Instagram. Instagram is a software that can create user-generated content and can be shared with other users. One of the tourism industries that is aggressively promoting through digital platforms is Fly Bali Heli. Fly Bali Heli is one of the popular tourist attractions in Badung Regency where many visitors use Fly Bali Heli tourism products even though the price is quite spectacular. The method used in this study uses a quantitative descriptive analysis method with a simple linear regression analysis technique. The sampling technique used in this study uses a purposive sampling technique with several criteria, with a sample size of 100 respondents. The results of this study indicate that Instagram social media has a positive and significant effect on visitors' purchasing decisions to buy tourism products at Fly Bali. Where Instagram social media has an influence of 30.8% on visitors' purchasing decisions to buy tourism products at Fly Bali.